Análisis hidrológico del sistema lagunar endorreico en la ciudad de Río Grande (provincia de Tierra del Fuego,Antártida e Islas del Atlántico Sur - Argentina) para proponer medidas de mitigación a la ocurrencia de tormentas de polvo - Perdomo, Santiago; Ruiz Cruz, María Dolores; Noir, Gerardo; Kruse, Eduardo Emilio (2021)
n the last decades, the city of Río Grande has been affected by the mobilization of sediments from dry lagoons near the urbanarea. The presence of airborne dust produces eye and respiratory diseases in the population, and limits land and air traffic in thecity, in addition to the degradation of natural resources. The aim of this work is to formulate a conceptual model of the lagoon system to understand the conditions in which sediment mobilization occurs and to propose mitigation actions. Climatic, hydrological and hydrogeological characteristics are then analyzed. To achieve this goal, a background review of geological andgeomorphological studies was carried out, a compilation and analysis of hydrometeorological information with emphasis on the temporal distribution and frequency of rainfall and wind (magnitude and direction). Field work included the recognition of the main sedimentary units, and sampling of surface water bodies and existing wells. In addition, a topographic leveling and ageoelectric prospecting were carried out to contribute to the geomorphological and hydrogeological analysis of the study area. The main results of this work defined the effluent behavior of surface water bodies in relation to the phreatic aquifer. The system is mainly regulated by groundwater with the contribution of climatic parameters. Finally, mitigation measures are proposed related to the management of surface and underground water resources, the control of livestock activity and the use of the soil to gradually reduce the presence of suspended sediments. En las últimas décadas la ciudad de Río Grande se ha visto afectada por la movilización de sedimentos provenientes del echo de lagunas ubicadas hacia el oeste y norte de la zona urbana. La presencia de polvo en suspensión produce afecciones oculares y respiratorias a la población, y limita el tránsito terrestre y aéreo de la ciudad, además de la degradación de los recursos naturales. El objetivo de este trabajo es formular un modelo conceptual del sistema lagunar a ...